Larangan Ber-KB sebagai Kontrol Reproduksi dalam Hukum Islam dan Gender - Syafura Nixie Diva Pamitravati; Citra Bunga Aulia; Siti Hadijah (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2025)
The ban on family planning in households is often viewed as a purely domestic matter, yet this practice has serious implications for the fulfillment of women's reproductive rights and bodily autonomy. Reproductive decisions are often shaped by unequal power dynamics, systematically denying women their right to make choices about their own bodies. This situation constitutes a form of reproductive coercion, namely the control of reproductive choices through pressure, prohibition, or manipulation, which is categorized as gender-based violence. This study aims to: (1) examine the prohibition on family planning as a manifestation of reproductive coercion and gender control; (2) analyze the position of this prohibition within the framework of the maqashid sharia; and (3) evaluate its implications for the protection of women's reproductive rights based on the principle of benefit in Islamic law. The method used is normative legal research with a conceptual approach and maqashid sharia, which is analyzed descriptively and qualitatively. The results of the study indicate that a unilateral ban on the use of family planning has no legitimacy in Islamic law because it contradicts the principle of deliberation and mutual consent in reproductive decisions. This prohibition contradicts the principle of public welfare, particularly the protection of life (hifz al-nafs), offspring (hifz al-nasl), and property (hifz al-mal). Furthermore, this practice conflicts with the principles of justice (adalah), the principle of non-harm (la dharara wa la dhirara), and the spirit of mu'asyarah bil ma'ruf (consensus of goodness) in marital relations. Therefore, the prohibition on family planning is not merely a private matter, but a form of reproductive control over women's bodies that must be critically examined and rejected from the perspective of gender-just Islamic law